The Effect Of Audio-Visual Daily Reminder On Medicine Treatment Compliance In Tuberculosis Patients In Puskesmas Garuda, Bandung City. - Vita Lucya; Melvi Sulistiawati (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
Tuberculosis is an infectious disease caused by TB germs. Adherence to treatment requires the patient's active participation in self-care management and collaboration between the patient and the health care provider. One way that can be done to improve compliance is with a daily reminder using audio-visual media. To find out how the daily reminder audio-visual effect on medication adherence in patients with tuberculosis. This research is a Quasi Experimental two Group Pre-Posttest Design with control group in May 2021 with 60 respondents in the working area of ??the Garuda Puskesmas Bandung City. Medication adherence was measured using the MMAS (Morisky Medication Adherence Scale) questionnaire with 8 question items. The description of the level of adherence to taking medication in the intervention group before being given an audio-visual daily reminder showed a low level of adherence (score <6) as many as 28 respondents (93.3%) and after being given the daily audio-visual reminder it increased to moderate adherence as many as 12 respondents. (40.0%) and high compliance 12 respondents (40.0%). The level of adherence to taking medication in the control group before being given the intervention showed low adherence by 15 respondents (50.0%) and after being given the leaflet the level of adherence remained in the low category as many as 13 respondents (43.3%). The results of this study indicate that there is a significant effect of the results of the daily reminder audio-visual intervention on medication adherence in tuberculosis patients